Effects of process parameters and scan strategy on the microstructure and density of stainless steel 316 L produced via laser powder bed fusion - Evangelou, Angelos; Stylianou, Rafael; Loizou, Alexandros; Kim, Donghyuk; Liang, Anqi; Reed, Philippa; Constantinides, Georgios; Kyratsi, Theodora (My University, 2023)
The ability to produce reliable and reproducible components from 316 L using additive manufacturing is crucial to serve the need for customization, on-demand manufacturing and reduced lead times for various industries. Laser powder bed fusion is becoming widely accepted as a versatile additive manufacturing technique capable of producing near defect-free components with tailored microstructures and mechanical properties. However, despite the recent progress in process parameter selection and optimization, even a small change in any of the laser parameters, equipment and feedstock powder characteristics can influence the microstructure and subsequently the mechanical properties of the fabricated parts. The purpose of this work is to tackle the process optimization challenge through, a full factorial design of experiments approach, to systematically assess the widely adopted energy density factor to evaluate the density of the final component. A statistical approach was also followed to evaluate potential plastic anisotropy in different samples produced with various energy densities and scan strategies. Density measurements indicated that beyond laser power and scan speed, the interaction effects of the aforementioned parameters with the layer thickness and the powder size distribution have a significant effect on the sample. Microstructural features such as melt pools, grains and crystallographic texture were characterized against a range of volumetric energy densities and scan strategies represented by different angles of rotation between successive layers. Smaller angles of rotation per layer were found to decrease texture anisotropy and suppress the formation of keyhole porosity in finer and more homogenous microstructures. The assessment of plastic anisotropy in the produced samples was evaluated using microhardness measurements on all three orthogonal planes of the samples. The hierarchical microstructure of laser powder bed fusion materials induces several strengthening mechanisms, that can simultaneously be activated depending on the loading scenario, location and plane.
Keywords: 316 L; Design of experiments; Laser powder bed fusion; Process parameters; Statistical analysis